Surgical Treatment Of Juxtarenal Occlusive Lesions Of The Aorta - Ishita Nirmala Raj, Morley D. Lacy, Shahriyar L. Candyce (Academic Journal of Clinicians, 2024)
Infrarenal aortic occlusion is defined as chronic total occlusion (CTO) of the aorta with or without involvement of the iliac arteries. It is classified as a TASC II (TransAtlantic Inter-Society Consensus) type D injury, represents 3 to 8.5% of aortoiliac occlusive diseases and can lead to ischemic symptoms in the lower limbs. We report the case of a patient with CTO of the proximal infrarenal (juxtarenal) aorta with occlusion of the iliac arteries and high surgical risk who was treated completely endovascularly. Surgical revascularization has been the treatment of choice for patients with this disease. Although the results of endovascular treatment are favorable for aortoiliac lesions, endovascular treatment of complex lesions, especially aortic CTO, remains very challenging.